LITERATURE REVIEW: ANALYSIS OF FACTORS INFLUENCING PURCHASING DECISIONS, PRODUCT QUALITY AND COMPETITIVE PRICING - Etty Zuliawaty Rajasa; Abdul Manap; Putu Doddy Heka Ardana; Muhammad Yusuf; Harizahayu Harizahayu (Jurnal Ekonomi, 2023)
Product quality is a combination of properties and characteristics that determines the extent to which the output can meet the conditions of customer needs. The purpose of this study is to analyze the factors that influence purchasing decisions, including product quality and competitive prices. This scientific article was written using qualitative methods, literature study, and library research. Reviewing literary books that are in accordance with the theory being discussed, especially in the context of strategic management. This includes reviewing both respected and less respected scientific articles from journals. Mendeley and Google Scholar serve as the sources for all scientific articles. Based on the discussion in this article, it can be concluded that: (1) product quality has a significant positive effect on purchasing decisions (2) Price has a significant positive effect on purchasing decisions.